Analysis of implications of organ donation on living donors in southeastern Iran: A qualitative study - R. S. Bahador; P. Mangolian; J. Farokhzadian; S. S. Afrazandeh; E. Nouhi (Вестник трансплантологии и искусственных органов)
Objectives: despite the annual increase in living donors and the positive and negative implications following organ donation, this issue had become a significant challenge for donors. The present study aimed to analyze the experiences and views of living donors to organ donation implications.Material and Methods. The present study was performed using qualitative content analysis. Twenty participants were selected using the purposive sampling method; data were collected by semi-structured interviews and analyzed based on Lundman and Graneheim contractual content analysis method after implementing MAX 12.Results. Data analysis elicitated 721 codes, 20 subcategories, six main categories, and two themes, including positive and negative implications of organ donation from the viewpoint of living donors. The main categories of positive effects resulting from organ donation included the «donor’s peace of mind», «fundamental strength», and «recipient’s achievements». On the other hand, the main categories of negative implications resulting from organ donation included «donor’s physical suffering», «damaged interactions», and «abandonment».Conclusion. Increasing the number of living donors makes us consider it essential to understand the efficiency of its two-way implications on many aspects of donor and recipient. Thus, managing the negative impacts of living organ donation and strengthening its positive side emphasizes the need to increase the awareness of organ donation associations, develop health policies at higher levels, and, most importantly, improve the satisfaction of live organ donors